Pengaruh Substitusi Pakan Konsentrat dengan Tepung Azolla terhadap Kualitas Semen Ayam Kampung - Reski, Reski; Awaluddin, Awaluddin; Khaeruddin, Khaeruddin; Syamsuryadi, Bahri; Hermawansyah, Hermawansyah (Universitas Islam Negeri Alauddin Makassar, 2026)
The aim of this study was to determine the effect of substituting concentrate using azolla flour (Azolla microphylla) in rations on the quality of native chicken semen. 10 adult male native chickens were used in this study as replications. Chickens were kept in individual cages with feed containing concentrate (P0) for 2 weeks then the semen was evaluated. Furthermore, they were kept for 2 weeks given a ration with azolla flour (P1) as a substitute for concentrate. Semen was collected by massage method and evaluated macroscopically and microscopically. Macroscopic research parameters were volume, color, pH, and consistency of semen, while microscopic parameters were motility, viability, abnormality and concentration of spermatozoa. This study used a paired T test with 2 levels of treatment, namely before azolla flour substitution (P0) and after azolla flour substitution (P1). The results showed that azolla flour substitution in rations was able to increase spermatozoa motility significantly (P <0.05) up to 88%. While other parameters showed that there was no difference in semen quality (semen volume, semen color, semen consistency, semen pH, spermatozoa viability, spermatozoa abnormalities and spermatozoa concentration) after administration of azolla compared to before administration of azolla (P>0.05). The semen quality obtained was semen volume 0.18-0.23 ml, milky white semen color, thick semen consistency, semen pH 7.47-7.58, spermatozoa viability 91.5-93%, abnormalities 10.2-19.7% and spermatozoa concentration 2.47-2.9 billion/ml.